Efikasi Diri Siswa Sekolah sebagai Layperson Pemberian Pertolongan Pertama Cedera - Nastiti, Eky Madyaning; Darotin, Rida; Ekaprasetia, Feri (Jurnal Kesehatan, 2023)
An injury can be experienced by anyone, regardless of age. Students are one of the most vulnerable groups. The school area is the second-highest injury area. Actions of first aid in the case of injury in the school environment become essential for students. To become the ideal layperson, a self-confidence is required as the foundation. The aim of this study was to identify the self-efficacy of junior high school children as laypersons in handling injury cases. This research was quantitative with a cross-sectional analytical-descriptive approach. The study was conducted in September 2022 at the junior high school (Sekolah Menengah Pertama/SMP) in Jember. A total of 239 students filled in the General Efficacy Scale questionnaire. The majority of the students’ self-efficiency rates as first-aid layperson in injury was in average rate of 60.1%, while those who have high self-efficacy was 20.8%, and a low one was 19.1%. When a school-age child giving first aid, it is necessary to pay attention to the child's age characteristics. In school-age children, characteristics are shown in relation to their cognitive skills according to reasoning and consciousness of the constantly developing self. To maximize the role of students as laypersons, one of the stimuli that can be done is by strengthening their cognitive possessions in order to align with the development of their self-efficacy, so that school-age children can prepare themselves as laypersons in injury management. One of the stimuli that can be done is to initiate first aid education in students. It is expected that education from an early age will prepare students for having self-efficiency in first aid.